Development tips and tricks application for DSLR beginner user / Mohamad Aliff Ahmad Sanusi - Ahmad Sanusi, Mohamad Aliff (2017)
The stakeholder for this project is Moon Photo Studio. Moon Photo Studio is a photography company based on Taiping, Perak. The company also want to help beginner user using DSLR with teach the basic of using DSLR. The problem statement is most of the user use full automatic mode because they lack of knowledge to setting their camera using the manual mode. The project requires a mobile application to detect light intensity and convert the light intensity to shutter speed, aperture, and ISO. The user can create a note and share with another user about photography. Admin from Moon Photo Studio can share tips about photography with the users. There were three objectives that need to be achieved in this project which were, to gather and analyses the user requirement, to design the Analog Meter and lastly to develop the Analog Meter system. This application focuses on beginner user to guide them using the manual mode. This project used the Mobile Application Development Life Cycle (MADLC) which consists of three phases which are the identification phase, analysis requirement, the design phase and the development phase which each of the phases had its own activities involved and the deliverables. Each phase has achieved each objective of the project. It is for seen that hope this application can help beginner user using DSLR camera. The enhancement is application also can provide some forum for a beginner user to share their picture that has been capture by using this application and get some feedback and comment on the picture by others users that use this application.